„Medalions” by Igor Severyanin – the Problem of the Translation to Polish Language (Analysis and Translation) - Bednarczyk, Anna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
The article concerns the problem of poetic translation of Igor Severyanin’s one hundred sonet cycle Medalions to polish. A brief review of the poet’s reception in Poland was conducted, taking in consideration his impact on polish futurists. In the course of the work, the difficulties related to the intertextualisation of the text, its saturation with neologisms and neosemantics, combination of innovative and traditional, as well as problems related to the translation of sonnets and the cycle, were also indicated. On the other hand, the possibilities given to the translator by the original text are shown: the similarity of cultures, the use of which contributes to the implementation of a good translation.